Synthesis and Characterisation of iron doped manganese oxides for thermal energy storage - Joseph Pandeinge Mwatukange; Ateeq Rahman; Zivayi Chiguvare (Results in Chemistry)
Iron-doped manganese oxides were synthesized using a co-precipitation method and thermodynamically characterized to demonstrate their potential as a thermochemical energy storage medium. Thermochemical energy storage, via chemical bonds that employ reversible redox reactions, is a promising approach to tackle solar thermal energy storage. Hysteresis loops observed confirm that the pore network consisted of mesopores that were not filled with pore condensate, and the narrow loop indicates a narrow size distribution. Barrett-Joyner-Halenda (BJH) studies of all the synthesized materials showed that they have a high mesoporous and specific area, essential for supplying reduced diffusion channels over the Mn oxides, Good conductivity through electron transfer, with the presence of active sites allow the study thermochemical approaches. The BJH studies showed the material MnOFe2 (2.5:1) to have a higher pore area, which is effective in the adsorption process of the material.